Successful living‐related kidney transplantation in a boy with inherited dysfibrinogenemia. (21st August 2013) - Imamura, Hideaki; Akioka, Yuko; Asano, Tatsuo; Sugawara, Noriko; Ishizuka, Kiyonobu; Chikamoto, Hiroko; Taki, Masashi; Terasawa, Fumiko; Okumura, Nobuo; Hattori, Motoshi
Abstract In kidney transplantation, it is essential to avoid acute vascular complications, such as hemorrhage and renal vascular thrombosis, which may often lead to allograft loss. Inherited dysfibrinogenemia is a rare coagulation disorder with a wide spectrum of clinical manifestations, such as excessive bleeding and thrombosis. A 12‐yr‐old boy, previously diagnosed with renal hypodysplasia, was found to have reduced fibrinogen concentrations. Coagulation tests assessing surgical risk during kidney transplantation showed a discrepancy between functional and immunologic fibrinogen concentrations. Gene analysis confirmed inherited dysfibrinogenemia, with a heterozygous mutation in FGA (Aα Arg16His) in the patient and his mother. Based on the molecular and functional properties of the mutation, and a familial phenotype, in which his aunt had experienced a previous bleeding episode, the patient was considered at greater risk of bleeding than of thrombosis. The patient was administered fibrinogen concentrate before surgery, and kidney transplantation was performed with his father as the organ donor. The patient received additional prophylactic infusions of fibrinogen concentrate postoperatively, and his postoperative course was uneventful. Accurate diagnosis of dysfibrinogenemia, including gene analysis, is important for correctly managing patients with this coagulation disorder who are undergoing kidney transplantation.